Karakterisasi Kromosom Stroberi (Fragaria vesca L. subsp. californica Cham. & Schltdl. cv. Californica) Hasil Poliploidisasi - Rosyidatul Khoiroh; Ganies Riza Aristya; Sutikno S; Niken Satuti Nur Handayani (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2015)
Fruit consumption such as strawberries always increase in Indonesia and reaching about 210 tons in 2011. Strawberry (Fragaria vesca L. subsp. californica Cham. and Schltdl. cv. Californica) has been developed in Indonesia, especially in Banyuroto, Sawangan, the district of Magelang, Central Java. In order to improve the fruit productivity (quality and quantity), geneticcharacterization including chromosomes character of this fruit are needed to be investigate. Therefore, the research was conducted to determine the chromosomes number, chromosomes size chromosomes shape and karyotype of control and strawberries treated by colchicine as mutagenic agent. The method was squash and flow cytometry method. Whereas the cell suspension samplewere observed used flow cytometer instrument. The result of research shown that the chromosome number of strawberry Californica in normal and treatment strawberries was 2n=14. Thechromosomes shape of normal strawberry was 10 metacentric and 4 submetacentric. Whereas the chromosomes shape of treatment strawberries used colchicine was 10 metacentric and 4submetacentric. Flow cytometric analysis shown that control strawberries and treated strawberries has diploid ploidy level.Keywords: chromosomes, colchicine, flow cytometry, polyploidization, strawberry Californica